The glass-like glazed coating made of cathode-ray tube faceplates cullet - N.І. Zavgorodnya; О.А. Pivovarov (Trudy Odesskogo Politehničeskogo Universiteta, 2016)
The tendency of the current time is to find ways of expedient municipal solid waste recycling as a secondary raw material with similar physicochemical and mechanical characteristics for the purpose of efficient use of resources and reduction of harmful impact on the environment. Due to the termination the production of monitors and television sets with cathode-ray tubes, a significant part of them is grow out of use in the form of dimensional waste. Kinescopes of these electric devices contain valuable components including the screen and conical glass and cathode-luminophors. Existing trends in the world of CRT faceplates cullet recycling argue for reasonability of recycling ways of this valuable secondary raw materials. Aim: The aim of researches is to determine the impact of the full replacement of quartz sand by faceplates cullet and using the zinc sulfide, reconstituted of used cathode-luminophors, as a secondary raw material in the production of glass-like glaze on the basic properties of color glaze. Materials and Methods: Cathode-ray tube faceplates are cut off during removal process, washed from dirt, dried, crushed by press, milled in a cheek grinder and finally crushed in a barrel mill. The slurried impurity (clay), dyes of desired color, including ZnS, water are added to this powder. The received mix is processed of wet grinding for slip production. Slip is surfaced on glass-ceramic tile, dried up, burned at maximum temperature of 900ºС. Results: Experimental research has shown that glass-forming, modifying and intermediate oxides of inorganic substances are added to the glaze with the CRT faceplates cullet. The Chasiv Yar clay belongs to the group with significant gas emission. The water vapor arising during the clay dehydration plays role of the "carrier" of heavy non-volatile components, considerably accelerates gas processes and increases activity of gas components. Zinc sulphide, dissolved in the silicate glaze melts when heated almost to the calcining temperature, gives it color. Properties of the obtained glaze, calculated according to the additivity law, confirm its satisfactory quality. Conclusions: Complete replacement of quartz sand by cathode-ray tube faceplates cullet in the production of glasslike glaze yielded a homogeneous glaze melt, shift the melting point with less viscous and satisfactory estimate indicators of glaze. The use of reconstituted zinc sulfide as a secondary raw material in the form of additives to the dyes of colored glaze caused by its solubility in melts of silicate glaze.